Visual media communication - Mandav, Pradeep (Delhi Authors Press, 2001)
Communications is the root to all human performances and interactions.Our country is witnessing the revolution of communication system via visual media. Changes have occured in the fields of education, training and distance communicationwhich are far beyo
Keywords: Visual communication; Communication; Visualization; Imagination